A new freeware program for the Probability of Success calculation of new gas discoveries within the Croatian part of the Po depression (Rudarsko-geološko-naftni zbornik, 2017)
The aim of this paper is to introduce an application in the form of a transparent freeware program which can be used for the assessment of the Probability of Success (abbr. POS, also POS and geological probability are synonyms) in finding new gas discoveries within the Croatian part of the Po depression. A deterministic approach is applied and includes five geological categories (traps, reservoirs, source rocks, migration and hydrocarbon preservation) with certain geological events that depend on the geological settings of the Northern Adriatic subsurface. The chosen probability classes include five, three or two numerical and textual values as follows: 1.00 for certain, 0.75 for very probable, 0.66 and 0.50 for reliable / probable, 0.33 and 0.25 for unreliable / low probable and 0.05 for not proven / improbable events. The program is made as an improvement in the sense of faster calculation according to a previous assessment that was based on a previously published Croatian model of the POS using Microsoft Excel and GeoProbe Modeling 1.1 program as an example, whichis used to calculate the geological probability of hydrocarbon discoveries for the Croatian part of the Panonian Basin System. The program is in English and it is done in the C# programming language.